FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA ANAK BALITA DI WILAYAH KERJA PUSKESMAS HELVETIA TAHUN 2017 - Bancin, Dewi; Sidabukke, Idaria; Rajani, Rajani (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
Each episode of diarrhea will caused loss of required nutrients for children to grow, so diarrhea is a major cause of malnutrition in children. According to data from Medan city health department, during 2009, indicates the incidence of diarrhea in infants is 20.708 cases, or 49 percent of the total cases round the year. This is due to lack of mothers knowledge about the dangers and prevention methods of diarrhea (northern Sumatra Department of Health, 2009). This study is an analytic survey with case control study, the cases are 60 children under five which suffering from diarrhea. The population in this study are all mothers with children under five in Sentosa Baru primary health care, Medan Perjuangan Disrict, Medan City, 2017. The variable in this study is the maternal knowledge, maternal habit of washing hands before feeding children, ages, sex, nutritional status of children, sewerage, clean water resources and family’s toilet. Data analysis using a univariate analysis, and bivariate analysis using Chi-square test. From the multivariate variables result that the incidence of diarrhea in children under five associated withmaternal knowledge (p = 0.00), maternal habit of washing hands before feeding children (p = 0.00), age(p = 0.00), sex (p = 0.01), the nutritional status of children (p = 0.00), sewerage (p = 0.00), resource ofclean water (p = 0.02), and family’s toilet (p = 0.03). Conclusion is there was an association betweenmaternal knowledge, maternal habit of washing hands before feeding children, ages, sex, nutritionalstatus of children, sewerage, clean water resources and family’s toilet with the incidence of diarrhea. It issuggested that made a counseling from primary health care officer to mother which had a children underfive about risk factors of diarrhea in children under five.